Distribution of Laryngopharyngeal Malignancy in the North-East Part of Bangladesh: Fiberoptic Laryngoscopic (FOL) Study of 300 Cases (Journal of Bangladesh College of Physicians and Surgeons, 2022)
Introduction: In Bangladesh, laryngeal and hypopharyngeal cancers in 2018 were 3.3% and 4.7% of total cancer cases, 2.6% and 2% of total cancer deaths. Fiber optic laryngoscopy (FOL) has been established as a valuable tool for diagnosis in outpatient department (OPD) setting. The primary objective of this study was to see the distribution of laryngeal and hypopharyngeal cancers and secondary objective was to assess the role of Flexible Endoscopic Biopsy (FEB) in the diagnosis of laryngopharyngeal cancers. Methods: This descriptive cross-sectional study was performed from March 2020 to March 2021 at Mount Adora Hospital, Sylhet, Bangladesh. All suspected patients attending in this hospital for FOL and FEB were included in this study.Results: Total 300 patients of laryngopharyngeal growth were included in this study. The age of the patients ranged from 25 to 100 years with a mean age of 58.1 year (SD=11.8). Male: Female ratio was 4.8:1. Hypopharyngeal growth was most common (47.3%) followed by laryngeal (31.7%) and tongue base growth (21%). In laryngeal growth, supraglottic was more common (69.47%). In hypopharyngeal growth, pyriform fossa was the most common site (88.3%). Synchronous pathology was found in two patients (0.67%). FEB was obtained from 95% of cases. Histopathological examination showed 95.85% positive for malignancy. Sensitivity of FEB was 95.8%. All malignancies were squamous cell carcinoma (100%).Conclusion: Supraglottic region is the most common site for laryngeal cancers and pyriform sinus is the most common site for hypopharyngeal cancers. FEB is highly sensitive in acquiring a definite diagnosis.J Bangladesh Coll Phys Surg 2022; 40: 99-104